Implementasi Nilai-Nilai Karakter Siswa dalam Pembelajaran Contextual Teaching And Learning (CTL) pada Pelajaran Tematik di SD Unggulan ‘Aisyiyah Taman Harapan Curup - Muslimah, Muslimah; Mutia, Mutia (AR-RIAYAH : Jurnal Pendidikan Dasar, 2018)
This research is motivated by the phenomenon of character education which lately has not been carried out optimally and the effectiveness of formal education has not been effective. Everywhere acts of violence and rounding or quarrels occur. This is very worrying for children. So that the teacher has an important role in forming and developing the character of students in the school environment, especially in carrying out learning activities. CTL learning is one of the learning models suitable for implementing student character education in thematic subjects. So the purpose of this study is to study more deeply about what character values are contained in thematic lessons through learning Contextual Teaching and Learning in Primary Elementary Schools ‘Aisyiyah Taman Harapan Curup and its implementation. This study uses a descriptive qualitative approach. Data collection techniques used in the form of interviews, observation, and documentation. Data analysis uses Miles and Huberman interactive models, namely data reduction, data presentation, and conclusion drawing. Test the validity of the data using triangulation techniques. The results of the research that have been carried out show that: (1) the character values in CTL learning in the thematic study of sub-themes 1 and 3 of learning 3 has 12 character values developed. These values are religious, disciplined, hard work, creative, independent, curiosity, love for the country, respect for achievement, caring for the social, responsible, friendly / communicative, and tolerance; (2) the form of character education implementation in CTL learning is realized in each thematic learning activity sub-themes 1 and 3 which are integrated with CTL aspects in it such as praying, praying, using learning media, conducting experiments, giving assignments, asking questions, presenting the results of the discussion, singing Indonesian songs, and doing practice questions.